Genetic counselling of young women with breast cancer for Li–Fraumeni syndrome: a nationwide survey on the experiences and attitudes of genetics professionals - Bakhuizen, J. J. (Fam Cancer, 2018)
Germline TP53 mutations are associated with an increased risk of early-onset breast cancer. Traditionally, it was not standard practice to offer TP53 genetic testing due to the low mutation detection rate and limited options regarding preventive screening. Recent guidelines recommend that all women diagnosed with breast cancer before the age of 31, irrespective of family history, should be offered TP53 genetic testing. This study aims to gain more knowledge on the attitudes and experiences among genetics professionals regarding the timing and content of genetic counselling of young breast cancer patients for Li–Fraumeni syndrome (LFS). We conducted a nationwide online survey among genetics professionals who provide cancer genetic counselling in the Netherlands. Fifty-seven professionals completed the questionnaire (response rate overall 54%, clinical geneticists 70%). Most respondents reported that they discuss the option of TP53 genetic testing—simultaneously with BRCA 1/2—during the initial counselling visit, especially in case of referral for treatment-focused genetic counselling. There was a general consensus about ten information items that should be discussed during counselling. Sixty-one percent of genetics professionals did not encounter difficulties in providing genetic counselling for LFS, but a substantial minority (29%) did. This study offers valuable insight, which will be useful for clinical practice. Studies which address young breast cancer patients’ attitudes and preferences regarding the timing and content of counselling are warranted to further determine the most appropriate genetic counselling strategy for these women.